رسالة الناسخ والمنسوخ للملا محمد بن آدم البالكي الروستي (1164-1237هــ) نقد وتحليل - الدين, بختيار نجم الدين شمس; محمود, محمود عبد الله (Sulaimani Journal for Humanities, 2022)
This letter, which is entitled: A Letter in the (al-Nasikh and al-Mansukh) Abrogater and Abrogated, is a writing of the Mullah Muhammad Ibn Adam al-Balaki al-Rosti (1164 - 1237 AH). After a great effort by the brothers at the Soran Manuscripts Center, they could obtain one copy, which is located in the library of the Manuscripts House in Baghdad. Despite the damaging effects of moisture and wetness which have reached them, and affected parts of them in a way that these parts cannot be read, but we decided to verify. We have divided the research into a preface and three sections. We dedicated the first section to introduce the Sheikh briefly. In the second section, the manuscript described nd we talked about the truth of referring the manuscript to the writer. In the third section, we recorded some comments on the letter and the writer's opinions.